2017
DOI: 10.17222/mit.2015.227
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of laminated steel-based composite materials fabricated by hot rolling

Abstract: The fabrication of laminated steel composites by hot rolling is described. Composite sandwiches were made from martensitic stainless tool steel with an increased nitrogen content and from standard AISI 304 steel using 3 to 7 layers. The maximum strength of the martensitic steel was 1370 MPa. The composite sheets had strengths in the range 950-1200 MPa, depending on the number of layers and the proportion of the steels. A metallographic observation of the fractures revealed that the first occurrence was fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Their strength depends on the type of materials used and is close to the average value of components' strength [3]. Also, the number of layers affects the properties of multilayered materials [4]. It has been shown that an increase in the number of layers up to a certain point improved the impact energy of multilayer sheet.…”
Section: Introductionmentioning
confidence: 86%
“…Their strength depends on the type of materials used and is close to the average value of components' strength [3]. Also, the number of layers affects the properties of multilayered materials [4]. It has been shown that an increase in the number of layers up to a certain point improved the impact energy of multilayer sheet.…”
Section: Introductionmentioning
confidence: 86%